Visceral analgesia induced by acute and repeated water avoidance stress in rats: sex difference in opioid involvement - LARAUCHE, Muriel (2012)
BACKGROUND: Chronic psychological stress-induced alterations in visceral sensitivity have been predominantly assessed in male rodents. We investigated the effect of acute and repeated water avoidance stress (WAS) on the visceromotor response (VMR) to colorectal distension (CRD) and the role of opioids in male and cycling female Wistar rats using a novel non-invasive manometric technique. METHODS: After a baseline VMR (1(st) CRD, day 0), rats were exposed to WAS (1h/day) either once or for 4 consecutive days, without injection or with naloxone (1 mg/kg) or saline injected subcutaneously before each WAS session. KEY RESULTS: The VMR to CRD recorded on day 1 or 4 immediately after the last WAS was reduced in both females and males. The visceral analgesia was mainly naloxone-dependent in females but naloxone-independent in males. In non-injected animals, on days 2 and 5, VMR was not significantly different from baseline in males while females exhibited a significant VMR increase at 60 mmHg on day 5. Basal CRD and CRD on days 1, 2 and 5 in both sexes without WAS induced similar VMR. CONCLUSIONS AND INFERENCES: When monitored non-invasively, psychological stress induces an immediate post-stress visceral analgesia mediated by an opiate signaling system in females while naloxone-independent in males, and hyperalgesia at 24 h after repeated stress only in females. These data highlights the importance of sex-specific interventions to modulate visceral pain response to stress.